Gender and Sexuality in Mathematics Education: Queer High School Students’ Experiences in the United States - Weverton Ataide Pinheiro (Boletim GEPEM)
In recent years, more research focusing on issues of gender and sexuality in mathematics education has been published. However, sexuality in mathematics education is still a largely unexplored topic. In this study, the experiences of groups historically targeted for the oppression of gender and/or sexual orientations are analyzed and discussed in the context of mathematics teaching and learning. Specifically, ten Queer-identifying high school students shared their experiences regarding their Queerness and mathematics after participating in interviews. Through qualitative analysis methodologies, this study provides a cohesive description and analyses of the discourses Queer high school students produced as they reflected on their experiences with mathematics. Through thematic analysis, findings show that mathematics teaching and learning are still disconnected from students' Queer identities and the real-world, and Queer students see a divide between Queerness and mathematics, which in many cases causes their exclusion from the STEM fields.